An Overview of Electricity Tarif Regulation - Croseffi, Mike (JURNAL BISNIS STRATEGI, 1999)
According to neoclassical economic  theory,competition  creates economic  efficiency,  which in turn result in the optimal prices  and allocation  of resoaurces across the economic. In practice, though, competitive  markets  do not work perfectly, or may be altogether impractical  (i.e. in the case of "natural monopolies " such as network infrastucture  like roads  and transmission lines).  Moreover. certain  economic activities are accompanied by externalities, which are impacts of the activity that are not included in the market price. Pollution  is a commonly cited externality.